Political Aspects of Digitalization and Networking of the State - D. Yu. Ivanov; V. A. Volkov (Управленческое консультирование, 2023)
The digitalization of the state is the object of close scientific discourse, especially in terms of the implementation of administrative reforms and the description of the storyline of the formation and development of new tools and forms in modern public administration. A meaningful analysis of an extensive layer of scientific publications shows that the digitalization of the state has acquired a mostly problematic connotation. It is worth fixing a significant lack of theoretical research regarding the comprehension and comparative analysis of international experience, as well as identifying trends in the development of state digitalization processes, which allow finding the keys to the most complete study of this phenomenon in the public administration system.   The purpose of the article is to answer the question about the role, factors and trends of digitalization of the state in the context of international and Russian experience.   Based on the conceptualization of the new public management, the authors analyze how exactly the phenomenon of digitalization is built into the modern model of political governance and what forms and characteristics it acquires. As a result, it is proposed to focus the attention of researchers on the institutional nature of the digitalization of the state, since it is political institutions that are the sources, mediators and main beneficiaries of digitalization processes.